Groundwater regime evolution in an excavation damaged zone of underground water-sealed petroleum storage caverns - Ya, Xianzhong; Liu, Xiaoli; Zou, Jing; Wang, Fang; Wang, Sijing; Zhang, Xinlei (Frontiers in Earth Science, 2026)
The excavation of underground engineering structures induces damage in the surrounding rock, resulting in the formation of an excavation damaged zone (EDZ) around the excavation profile. The evolving EDZ will alter the permeability of the surrounding rock mass and thus lead to a changing seepage field. In this article, underground water-sealed petroleum storage caverns are taken as study objects. Based on the measured fractures in the field, a random fracture network simulation technique is used to study the initial permeability characteristics. In addition, the occurrence of the EDZ and its evolution are studied. Combining the initial permeability with the EDZ-induced permeability alteration, and the rainfall process considered, the changing 3D seepage field is analyzed numerically. Water inflow into the cavern working face is predicted, and the influence of excavation on the groundwater table is examined. The results show that the simulation values of the groundwater table agreed well with the monitored ones, considering the effect of cavern excavation. As groundwater conditions are critical to the effectiveness and safety of petroleum storage, investigating the evolution of the groundwater regime during excavation is essential for optimizing construction sequencing and designing reliable water-sealing conditions during operation.